Analisis Peran Kepala Sekolah dalam Meningkatkan Mutu Pendidikan: Studi Literatur - Akhmad Suyatno; Perawati Silalahi; Akmal Syah (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the role of the principal in improving educational quality through the implementation of managerial functions. It employs a qualitative approach using a literature review of 20 articles from national and international journals published between 2021 and 2025. The findings reveal that the application of planning, organizing, actuating, and controlling functions contributes to improving teacher competence, learning effectiveness, and students’ character development. The principal’s role extends beyond academic achievement to include moral values and life skills. Unlike previous studies that generally discuss leadership roles, this study highlights the integration of managerial functions and the principal’s educational role as a key contribution to improving educational quality.